Improved mechanical and electrical properties of copper-aluminum joints with highly aligned graphene reinforcement via friction stir spot welding - Mohammad Syahid Mohd Isa; Mohd Ridha Muhamad; Farazila Yusof; Nukman Yusoff; Zbigniew Brytan; Tetsuo Suga; Yoshiaki Morisada; Hidetoshi Fujii (Journal of Materials Research and Technology, 2023)
This study demonstrates the potential of friction stir spot welding (FSSW) for producing highly aligned graphene configurations in copper-aluminum joints, resulting in improved mechanical and electrical properties. Pure copper and AA6061 sheet were welded with 0.5% graphene nanoparticles dispersed in ethanol drop cast at the interface. Under optimized experimental conditions, adding a graphene interlayer results in a 15.6% increase in maximum shear strength, a 46% increase in hardness value, and a 23% reduction in joint electrical resistance. Transmission electron microscopy confirmed that the laminar flow behavior of the material aligns the graphene nanoparticles parallel to the tool surface direction. The mechanical improvements are attributed to the reduction of grain size and the plastic incompatibilities that arise at the metal-graphene interface. The highly aligned graphene configuration provides more conductive paths and acts as a bridge between grains to reduce grain boundary resistance, reducing electrical resistance. These findings pave the way for exploring the possibilities of utilizing the anisotropic properties of graphene in material joining applications.